Sucralose inhibited cell survival through the activation of ER stress in human endothelial progenitor cells - Chia-Ying Li; Hung-Yu Lin; En-Pei Isabel Chiang; Hung-Chang Hung; Feng-Yao Tang (PLoS ONE, 2026)
Sucralose, a widely utilized non-caloric sweetener, is frequently added to food and beverage products as a sugar substitute aimed at lowering energy consumption and reducing obesity-related health risks. However, epidemiological studies have indicated a possible association between high intake of sucralose and increased prevalence of coronary artery disease (CAD). Prior research has demonstrated that diminished levels of circulating human endothelial progenitor cells (hEPCs) are linked to a higher risk of CAD. Although sucralose is broadly consumed, its direct biological impact on hEPCs has not been comprehensively characterized. In this study, we investigated the cellular effects of sucralose on hEPCs using a variety of in vitro techniques, including assays for viability, migration, capillary-like tube formation, lactate dehydrogenase (LDH) release-cytotoxicity assay, and protein expression profiling by Western blotting. Our results revealed that increased concentrations of sucralose significantly impaired hEPCs viability, motility, and neovasculogenic function, accompanied by increased expression of markers associated with apoptosis, inflammasome activation, and pyroptosis. Mechanistic analysis further demonstrated that sucralose strongly activated endoplasmic reticulum (ER) stress/PERK pathways in these cells. Inhibition of ER stress via 4-phenylbutyric acid (4-PBA) substantially attenuated sucralose-induced cell death and reduced the expression of pyroptosis-related proteins and inflammasome markers. Taken together, these findings suggest that sucralose disrupts hEPCs function in part by triggering ER stress, which promotes both apoptotic and pyroptotic cell death programs.